Income and Expenditures of the Organization: Analysis and Optimization (on the Example of GUSP MTS "Central" RB) ("Journal "U". Economy. Management. Finance.", 2021)
The relevance of the article is due to the importance of the analysis of income and expenses for organizations of all forms of ownership as a way to establish ways and means of increasing profit and profitability. Since the main purpose of each business is to generate profit, a thorough analysis of revenues and expenses is fundamental. On the example of GUSP MTS «CENTRAL», RB analyzed revenues and expenses, as well as suggested ways to optimize them.
Keywords: income; expenses; enterprise; methodology; efficiency; activity